Pengaruh profitabilitas, kepemilikan manajerial dan leverage terhadap income smoothing - Yunitasari, Nur Ajizah; Agustiningsih, Wulandari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to analyze the effect of profitability, managerial ownership and leverage on income smoothing. Data analysis techniques in this study include descriptive statistical tests, and also logistic regression analysis. In this logistic regression analysis, it is necessary to test the feasibility of the regression model, the overall assessment of the model, and the coefficient of determination. Based on the results of research and analysis, it is known that simultaneously the variables of profitability, managerial ownership and leverage have an effect on the practice of income smoothing. Partially, the results obtained from this study are that profitability has a positive effect on income smoothing, managerial ownership has a positive effect on income smoothing, and leverage has a negative effect on income smoothing.